Analyzing Digital Platforms Appropriation to Support Organization Communication through Industry 5.0 Paradigm - Saman, Michel Gougou (Journal of Communication and Public Relations, 2023)
The digital revolution through the Internet, connected technologies, and virtual platforms transforms whole human activities including policies, the economy, education, the environment, and so on. Thus, in developed and developing countries particularly, social media and digital platforms appropriation results in virtualization of daily communication practices for human wellbeing in society and organizations. This paper aims to describe how digital platforms like social media transform organization strategies according to the exploration of Industry 5.0 as human centric paradigm to promote business activities resilience and build a social capital in a challenging context.  Through a virtual ethnography case study in Cote d’Ivoire, a West Africa Country, observation, interviews and focus groups allowed to collect data from a convenience sample of business owners/managers, employees and clients in 5 start up or enterprises from January to May 2024. Findings underline digital platform marketing strategies adoption, challenges encountered and outcomes for organization stakeholders in term of resilient value creation, and sustainability and human well-being. As recommendation, a communication development approach based on binding communication, social media marketing and Industry 5.0 paradigm is a strategic approach for effective communication in this changing world according to a human centric perspective. This can allow to create business opportunities, reduce poverty, increase resilience, balance organization sustainability through intelligent marketing communication tools and social media platforms integrated human activities